2021
DOI: 10.1186/s41610-021-00194-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-deep physiological dormancy in seeds of Euphorbia jolkinii Boiss. native to Korea

Abstract: Background Euphorbia jolkinii Boiss. is a perennial species native to Jeju Island and the southern coastal area of Korea. Particularly on Jeju Island, the yellow flowers of E. jolkinii Boiss. have a high ornamental value because of their contrast with basalt. This study was conducted to investigate the effects of different temperatures (5, 15, 20, and 25 °C) and gibberellic acid (GA3) concentrations (0, 10, 100, or 1000 mg/L) on seed dormancy and germination of E. jolkinii. In addition, we clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The shape of its seeds varies, the average size of seeds was 1.15 × 0.81 mm (length × width), and the structure of the embryo was assumed to be a fully developed miniature axile shape. Generally, seeds with MD or MPD have small and underdeveloped embryos [16,27,28] and the ratio of E:S is 0.5 or less [29]. We confirmed that the E:S ratio in L. coreana seeds was 0.84 ± 0.04.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The shape of its seeds varies, the average size of seeds was 1.15 × 0.81 mm (length × width), and the structure of the embryo was assumed to be a fully developed miniature axile shape. Generally, seeds with MD or MPD have small and underdeveloped embryos [16,27,28] and the ratio of E:S is 0.5 or less [29]. We confirmed that the E:S ratio in L. coreana seeds was 0.84 ± 0.04.…”
Section: Discussionsupporting
confidence: 72%
“…Whereas those that underwent WS at 25/15 • C did not germinate or had very low germination rates under most incubation condition (Table 1, S1). Therefore, dormancy type of L. coreana seeds are closer to non-deep PD than intermediate PD (require CS treatment with 2-3 months) [29]. The CS of seeds naturally occurred when they are exposed to consistent temperatures of 0-1 • C in snow-covered soil over the winter.…”
Section: Discussionmentioning
confidence: 99%
“…In the seed dormancy classification system of Baskin and Baskin (2021), the response of seed germination to dry storage treatment is also one of the indicators of the level of PD, that is, dry storage treatment can promote germination of some seeds with non-deep PD and shorten the time of cold moist stratification treatment of seeds with intermediate PD but has no effect on seeds with deep PD (Baskin and Baskin, 2014;Oh et al, 2021). In this study, the dry storage treatment for 8 months at 20 °C significantly promoted the germination of T. hassleriana seeds at 5-15 °C but extended the time of the subsequent cold moist stratification treatment (Figure 3, Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Alternating temperatures generally promote seed germination more than constant temperatures (Baskin and Baskin, 2004;Forti et al, 2020). An alternating temperature treatment can increase the level of germination-promoting phytohormones and decrease the level of germination-inhibiting phytohormones (Huarte et al, 2014;Özden et al, 2021). Compared to the initial germination of freshly harvested T. hassleriana seeds at constant temperature , the 20 °C/30 °C alternating temperature treatment could effectively release seed dormancy and promote germination, regardless of alternating light or darkness, whereas the germination rate in alternating light was significantly higher than that in darkness (P < 0.05), being more than 90%, while the 15°C/25°C alternating temperature treatment did not show a significant effect on seed germination (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Phytohormones are widely used during dormancy-break and germination of seeds. Among them, exogenous GAs such as GA 3 , GA 4 , GA 7 , and GA 4+7 , have been used to overcome PD or MPD, enhance germination, promote embryo growth, and stimulate radicle emergence in many plant species [20][21][22][23][24][25][26]. However, GAs does not enhance germination in all plant species, and seed germination may be inhibited depending on the method, immersion time, and/or concentration of GA solution used.…”
Section: Introductionmentioning
confidence: 99%